Lifecycle scenario design for product end-of-life strategy - Shinichi Fukushige; Kazuhiro Yamamoto; Yasushi Umeda (Journal of Remanufacturing, 2012)
This paper proposes a method for supporting the design of product lifecycles. The main approach involves supporting designers in determining a lifecycle strategy by describing lifecycle scenarios at an early stage of lifecycle design. The authors define a representational scheme for the lifecycle scenario and outline a support system based on the idea of the Cognitive Design Process model allowing the designers to examine various possibilities of lifecycle strategy. A number of alternative scenarios are managed by the Truth Maintenance System implemented in this approach. Finally, in order to embody the strategy in the later stages, the system derives requirements for product and process design. This paper outlines the lifecycle scenario of a cellular phone as a case study, which indicates the system's suitability for computer-aided description of scenarios and its facilitation of lifecycle strategy development.
Keywords: 650; lifecycle design; end-of-life strategy; lifecycle scenario; Produktlebenszyklus; Produktgestaltung; Produkt-Recycling; Strategisches Management